2021
DOI: 10.1038/s41598-021-85047-2
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the multi-scale structure–property relationship of laser powder bed fusion processed and heat-treated AlSi10Mg

Abstract: Tailoring heat treatments for Laser Powder Bed Fusion (LPBF) processed materials is critical to ensure superior and repeatable material properties for high-end applications. This tailoring requires in-depth understanding of the LPBF-processed material. Therefore, the current study aims at unravelling the threefold interrelationship between the process (LPBF and heat treatment), the microstructure at different scales (macro-, meso-, micro-, and nano-scale), and the macroscopic material properties of AlSi10Mg. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 43 publications
4
55
0
3
Order By: Relevance
“…Several scientific papers, in fact, were recently focused on heat treatments of LPBF AlSi7Mg0.6, and the current state of the art on this topic can be summarized as follows: (1) conventional T6 treatment, [13,14] (2) T6 treatment with a shortened solution treatment (0.25, 1, 2 hours), [14][15][16] (3) direct aging from the as-built condition at the conventional aging temperature of 160 to 165°C, [14,15,17] and (4) stress-relieving treatment performed at 300°C 9 2 to 3 hours. [13,16,18,19] The scope of direct aging and T6 treatment is to induce alloy strengthening. On the other hand, stress relieving is usually recommended to avoid deformations of the as-printed parts when separated from the building platform.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific papers, in fact, were recently focused on heat treatments of LPBF AlSi7Mg0.6, and the current state of the art on this topic can be summarized as follows: (1) conventional T6 treatment, [13,14] (2) T6 treatment with a shortened solution treatment (0.25, 1, 2 hours), [14][15][16] (3) direct aging from the as-built condition at the conventional aging temperature of 160 to 165°C, [14,15,17] and (4) stress-relieving treatment performed at 300°C 9 2 to 3 hours. [13,16,18,19] The scope of direct aging and T6 treatment is to induce alloy strengthening. On the other hand, stress relieving is usually recommended to avoid deformations of the as-printed parts when separated from the building platform.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Unfortunately, literature data showed that the common stress-relieving treatment can be detrimental for hardness and tensile properties. [13,16,18,19] It is worth mentioning that a systematic study comparing all the above-discussed treatment conditions for the AlSi7Mg0.6 (A357) alloy, one of the most widely used casting Al alloys, is currently lacking. Moreover, a common practice to reduce residual stress and cracking is pre-heating the building platform at a temperature between 100°C and 200°C for the entire process, as adopted by many of the mentioned experimental works.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high strength/weight ratio, lighter weights, and higher corrosion resistance of aluminum alloys enable their easy replacement for other materials in different engineering applications [4]. Recently, additive manufacturing (AM) technologies have been applied for 2 of 28 fabricating lightweight parts of simple and complex shapes to be used by different engineering sectors.…”
Section: Introduction 1additive Manufacturingmentioning
confidence: 99%
“…The overall AlSi10Mg alloy properties make the material ideally suitable for processing using the laser powder bed fusion (LPBF) AM technology and adoption of the alloy by many industries, including the aerospace and automotive sectors [4][5][6]. To ensure the high quality of printed specimens, it is essential to understand the impact of both the LPBF process parameters and the material feedstock properties on the quality of the parts [7], including the plastic anisotropic behavior; a notable lower ductility is typically observed for the vertical printed tensile samples when compared to their respective horizontal samples [4][5][6][7][8]. Namely, the study of the unique LPBF solidification conditions and the material's thermal history may lead to the understanding of the characteristic defects (porosity, hot cracking phenomena, and surface roughness), observed in AlSi10Mg alloy components produced by the LPBF technique [6,7].…”
Section: Introduction 1additive Manufacturingmentioning
confidence: 99%